Keterampilan Proses Sains Mahasiswa Pendidikan Fisika STKIP Nurul Huda pada Mata Kuliah Optika - Effendi, Effendi; Rosa Sinensis, Arini; Widayanti, Widayanti; Firdaus, Thoha (Universitas Nurul Huda, 2021)
This study aims to determine the Science Process Skills (KPS) of Physics Education Study Program Students in the Optics Subject. This research uses a descriptive method. The analyzed consists of 9 indicators including observing, clarifying, interpreting data, predicting, hypothesizing, analyzing, planning, experimenting / researching, using tools and materials, applying concepts and communicating. The results showed that the Science Process Skills as a whole obtained an average score of 84.10% in the very good category. Thus it is very clear that KPS Physics Education student STKIP Nurul Huda has excellent skills so that it has a positive effect on the development of student thinking patterns and attitudes which will ultimately have an impact on student success in learning..